NK cells-derived extracellular vesicles potency in the B cell lymphoma biotherapy - Cecchetti, Serena; Federici, Cristina; Canese, Rossella; Iorio, Egidio; Huber, Veronica; Pisanu, Maria Elena; Chirico, Mattea; Iessi, Elisabetta; Camerini, Serena; Casella, Marialuisa; Matteucci, Andrea; Macchia, Daniele; et al. (Frontiers in Immunology, 2024)
IntroductionExtracellular vesicles of Natural Killer cells (NKEV) exert an antitumor effect towards hematopoietic and solid tumors and have an immune modulating effect, suggesting a promising role in immune and biotherapy. In this study, a continuation of our former works, we demonstrated a network by mass spectrometry analysis between NKEV protein cargo and antitumor effects. Human healthy NKEV, both exosomes and microvesicles, have a significant and direct cytotoxic effect against human B cell lymphoma in in vitro and in vivo conditions.MethodsWe isolated extracellular vesicles from in vitro amplified healthy human NK cells and their treatment efficacy was monitored by cytometry analyses, in vivo MRI/MRS measurements, ex vivo MRS analyses and immunohistochemistry.ResultsWe observed a remarkable NKEV cytotoxic effect, mainly by apoptosis, on B cell lymphoma in vitro when exosomes and microvesicles were administered simultaneously. In vivo results showed metabolic alterations in SCID mice xenografts after NKEV treatment, associated with a significant reduction of tumor growth (64%). In the in vivo1H MR spectra we found a significant increase in the tumor lipid/lactate and in taurine signals, both considered as apotosis markers. Ex vivo lymphoma metabolomics revealed a significant increase in fatty acid (FA) pool and decrease in unsaturated and mono-unsaturated FA in treated groups, as compared to control one, thus suggesting an alteration of tumor homeostasis. Immunohistochemistry analyses confirmed the reduction of B-cell lymphoma proliferation rate, as well as the induction of apoptosis following the NKEV treatment. ConclusionsThis study underscore the importance of NKEV as a novel biological acellular tool for B-cell lymphoma treatment, probably having a greater effect on combined treatment regimens. These nanovesicles have an extraordinary potential in innovative cancer immunotherapy, representing a safe and efficient tool naturally circulating in healthy individuals and ready to maintain the immune homeostasis, and therefore a good organism healthy state.